Incorporation of silver nanoparticles (AgNPs) with endophytes cell-free secondary metabolites enhances antimicrobial activity - Ahmad Syairazie Ibrahim Fikri; Irman Abdul Rahman; Ainon Hamzah; Norefrina Shafinaz Md Nor; Siti Noor Adnalizawati Adnan (Malaysian Society of Applied Biology, 2024)
Indexed by Scopus